Unlocking Reading Potential: The Impact of Reciprocal Teaching on EighthGrade Students At MTs Al-Khairiyah Cilegon - Yuliyanti, Novy (Indonesian Research Journal on Education, 2024)
The purpose of this study is to determine whether the Reciprocal Teaching (RT) technique may improve reading comprehension in eighth-grade students at MTs Al-Khairiyah Cilegon. Employing a quasi-experimental design, two groups were compared: one taught using the RT strategy and the other using conventional teaching methods. Quantitative analysis revealed that the RT group achieved a significantly higher mean score (84.50) compared to the control group (78.00). Additionally, the RT group exhibited more consistent performance, as indicated by lower standard deviation and variance values. These findings are consistent with existing literature, which underscores the benefits of RT in promoting critical thinking, metacognitive skills, and collaborative learning. The study concludes that RT is an effective pedagogical tool for improving reading comprehension. Recommendations include integrating RT into school curricula, providing professional development for teachers, allocating resources for RT implementation, and conducting further research on its long-term effects. By adopting these recommendations, educational institutions can enhance students' reading comprehension and overall academic performance, making RT a valuable addition to instructional.